Some aspects of analysis of the Ukrainian legislation regulating the production of veterinary medicines - I. V. Bushuieva; K. V. Petrova; Zh. M. Polova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2021)
The aim of the work was to study the current state of domestic legislation of state regulation in the field of licensing the activities of business entities manufacturing veterinary medicinal products and its harmonization with the requirements of the European Union.